Transcriptome Analysis of ppdnmt2 and Identification of Superoxide Dismutase as a Novel Interactor of DNMT2 in the Moss Physcomitrella patens - Singh, Darshika; Yadav, Radha; Kaushik, Shubham; Wadhwa, Nikita; Kapoor, Sanjay; Kapoor, Meenu (Frontiers in Plant Science, 2020)
DNMT2 is a DNA/tRNA cytosine methyltransferase that is highly conserved in structure and function in eukaryotes. In plants however, limited information is available on the function of this methyltransferase. We have previously reported that in the moss Physcomitrella patens, DNMT2 plays a crucial role in stress recovery and tRNAAsp transcription/stability under salt stress. To further investigate the role of PpDNMT2 at genome level, in this study we have performed RNA sequencing of ppdnmt2. Transcriptome analysis reveals a number of genes and pathways to function differentially and suggests a close link between PpDNMT2 function and osmotic and ionic stress tolerance. We propose PpDNMT2 to play a pivotal role in regulating salt tolerance by affecting molecular networks involved in stress perception and signal transduction that underlie maintenance of ion homeostasis in cells. We also examined interactome of PpDNMT2 using affinity purification (AP) coupled to mass spectrometry (AP-MS). Quantitative proteomic analysis reveals several chloroplast proteins involved in light reactions and carbon assimilation and proteins involved in stress response and some not implicated in stress to co-immunoprecipitate with PpDNMT2. Comparison between transcriptome and interactome datasets has revealed novel association between PpDNMT2 activity and the antioxidant enzyme Superoxide dismutase (SOD), protein turnover mediated by the Ubiquitin-proteasome system and epigenetic gene regulation. PpDNMT2 possibly exists in complex with CuZn-SODs in vivo and the two proteins also directly interact in the yeast nucleus as observed by yeast two-hybrid assay. Taken together, the work presented in this study sheds light on diverse roles of PpDNMT2 in maintaining molecular and physiological homeostasis in P. patens. This is a first report describing transcriptome and interactome of DNMT2 in any land plant.